Using Electromagnetic Signal Propagation Models for Radio and Television Broadcasts: An Introduction. (1st June 2018) - Crabtree, Charles; Kern, Holger L.
Abstract : This note offers an introduction to electromagnetic signal propagation models, which can be used to model terrestrial radio and television signal strength across space. Such data are useful to social scientists interested in identifying the effects of mass media broadcasts when (i) individual-level data on media exposure do not exist or when (ii) media exposure, while observed, is not exogenous. We illustrate the use of electromagnetic signal propagation models by creating a signal strength measure of military-controlled radio stations during the 2012 coup in Mali.